KINERJA PENYULUH PERTANIAN LAPANGAN (PPL) DALAM PENGEMBANGAN BERAS ORGANIK MENUJU TERWUJUDNYA KABUPATEN SUKOHARJO SEBAGAI SENTRA BERAS ORGANIK - Kusriani Prasetyowati (JURNAL ILMIAH AGRINECA, 2012)
This research was conducted in Mojolaban Regency in which performance field extention workers very determining efficacy Mojolaban Regency as biggest organic sentra rice in the year 2010. So this research aimed at observing performance of filed extensions workers spacious in rice organic program. In this research performance filed extensions workers in organic rice program in Mojolaban Regency seeing from indicator such as reability, responsiveness, assurance, emphaty and tangible. Proportion analysis test showed all value from indicator used give the result to accepted hypothesis zero (HO) and refused alternative hypothesis (H1). It’s mean research hypothesis inferential unprovable, so performance field extentions workers in organic rice program it’s bad/low